(untitled) (Modern Information Technologies and Innovation Methodologies of Education in Professional Training Methodology Theory Experience Problems, 2011)
In the article the actuality question of introduction of sports and recreational work is examined in the fixedprocess of schoolboys. Certainly a ready of future teachers of physical culture condition is to practical work in thisdirection.